2006
DOI: 10.1002/app.24860
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of synthetic conditions of a novel collagen‐based superabsorbent hydrogel by Taguchi method and investigation of its metal ions adsorption

Abstract: A novel biopolymer-based superabsorbent hydrogel was synthesized through chemical crosslinking by graft copolymerization of partially neutralized acrylic acid onto the hydrolyzed collagen, in the presence of a crosslinking agent and a free radical initiator. The Taguchi method, a robust experimental design, was employed for the optimization of the synthesis reaction based on the swelling capacity of the hydrogels. This method was applied for the experiments and standard L 16 orthogonal array with three factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The results showed that the higher the porosity the higher the water absorbency. This indicated how effective factors influence the porosity 27…”
Section: Resultsmentioning
confidence: 92%
“…The results showed that the higher the porosity the higher the water absorbency. This indicated how effective factors influence the porosity 27…”
Section: Resultsmentioning
confidence: 92%
“…31 Nanosized magnetic materials are recently developed and it has 32 applications in many fields including separation, drug delivery, 33 tissue engineering [11][12][13] etc. The magnetic materials with 34 modified surface functionalities are recently been developed for 35 removal of heavy metals and dyes from aqueous solution [14][15][16]. 36 Hydrogels, a three dimensional polymeric materials can be used as 37 a template for the synthesis of magnetic nano particles and 38 structures.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have been researched for use in many applications, such as disposable diapers, agriculture, wastewater treatment, and drug delivery systems, because of their high absorption level of water and aqueous fluids including biological fluids. Due to their biocompatibility, biodegradability, renewability, and nontoxicity, natural compound‐based hydrogels have recently been synthesized with the emphasis on the use of natural polymers as a starting material, such as starch, gelatine, chitosan, protein, and collagen . Natural compound based hydrogels can be synthesized by grafting vinylic monomers onto the backbone of natural polymers in the presence of a crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%